PAX6 promoter methylation correlates with MDA-MB-231 cell migration, and expression of MMP2 and MMP9 - Urrutia, Guillermo Alejandro (2018)
Objective: Breast cancer is a heterogeneous disease characterized by an accumulation of genetic and epigenetic alterations that lead tumor cells to acquire characteristics like the capacity for invasion and metastasis. Metastasis remains a major challenge in cancer management and understanding of its molecular basis should result in improved prevention, diagnosis, and treatment of breast cancer patients. The aim of this study was to investigate how promoter DNA methylation regulates PAX6 gene expression and influences breast carcinoma cell migration. Methods: PAX6 promoter methylation was detected by Methyl Specific-Multiplex Ligation Probe Amplification (MS-MLPA). Gene expression was evaluated using qRT-PCR, while the effect of PAX6 on migration was ssessed by wound healing assay. In addition, MMP2 and MMP9 genes were studied using different bioinformatic tools. Results: The PAX6 promoter is methylated in breast cancer cell lines and methylation in this region impacts on its expression. Migration assays revealed that PAX6 overexpression promotes cell migration, while PAX6 inhibition decreases it. More importantly, we found that migration is affected by PAX6 methylation status. Employing bioinformatic analysis, binding sites for PAX6 on the regulatory regions of the MMP2 and MMP9 genes were established, PAX6 overexpression increasing MMP2 and MMP9 expression at the mRNA level. Conclusion: Our study provides novel insights into epigenetic events that regulate PAX6 expression and molecular mechanisms by which PAX6 modifies the migration capacity of breast cancer cells.